2013
DOI: 10.1371/journal.pone.0074030
|View full text |Cite
|
Sign up to set email alerts
|

The bZIP Protein MeaB Mediates Virulence Attributes in Aspergillus flavus

Abstract: LaeA is a fungal specific virulence factor of both plant and human pathogenic fungi. Transcriptional profiles of laeA mutants have been successfully exploited to identify regulatory mechanisms of secondary metabolism in fungi; here we use laeA mutants as tools to elucidate virulence attributes in Aspergillus flavus. Microarray expression profiles of ΔlaeA and over-expression laeA (OE::laeA) were compared to wild type A. flavus. Strikingly, several nitrogen metabolism genes are oppositely mis-regulated in the Δ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…The protein NmrA was defined as a repressor of the GATA transcription factor AreA, which regulates several genes required for utilization of less preferred nitrogen sources (Caddick et al, 1986; Andrianopoulos et al, 1998; Tudzynski, 2014), and the bZIP protein MeaB was proposed to activate NmrA in A. nidulans (Wong et al, 2007; López-Berges et al, 2010; Amaike et al, 2013). AreA, MeaB, and NmrA and are conserved in filamentous fungi (Wagner et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The protein NmrA was defined as a repressor of the GATA transcription factor AreA, which regulates several genes required for utilization of less preferred nitrogen sources (Caddick et al, 1986; Andrianopoulos et al, 1998; Tudzynski, 2014), and the bZIP protein MeaB was proposed to activate NmrA in A. nidulans (Wong et al, 2007; López-Berges et al, 2010; Amaike et al, 2013). AreA, MeaB, and NmrA and are conserved in filamentous fungi (Wagner et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies showed that nmrA expression in A. nidulans and F. fujikuroi is not MeaB-dependent (Wagner et al, 2010; Amaike et al, 2013), and MeaB and AreA mediate nitrogen repression coordinately while also functioning independently (Wong et al, 2007; Wagner et al, 2010). Moreover, the ability of AreA and AreB to respond to carbon status probably depends on NmrA rather than the transcription factor CreA, which mediates CCR in A. nidulans (Macios et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…bZIPs associated with SM regulation and stress include RsmA regulating sterigmatocystin and asperthecin in A. nidulans and gliotoxin in A. fumigatus [64,65], AtfB regulating aflatoxin in Aspergillus parasiticus [60], and Aoyap1 regulating ochratoxin in Aspergillus ochraceus [59]. The bZIP protein MeaB, involved in nitrogen regulation, has also been associated with regulation of SMs including bikaverin in F. fujikuroi and AF in A. flavus [62,63].…”
Section: Cys 2 Hismentioning
confidence: 99%
“…Among the regulators, several bZIP transcription factors mediate virulence and secondary metabolism [29]. In A. flavus, bZIP TF MeaB regulates secondary metabolism and virulence [30]. AtfB regulates aflatoxin production by binding to the promoters of seven aflatoxin biosynthesis genes that carry CREs [10].…”
mentioning
confidence: 99%